Hyaluronic Acid Compound Filling Plus Mesotherapy vs Botulinum Toxin A for the Treatment of Horizontal Neck Lines: A Multicenter, Randomized, Evaluator-Blinded, Prospective Study in Chinese Subjects. (10th November 2021) - Li, Yiming; Liao, Meirong; Zhu, Yijin; Gao, Jie; Song, Yang; Zhai, Yang; Zhu, Miao; He, Yan; Dong, Weiwei
Abstract: Background: Although energy devices and botulinum toxin A (BTX-A) can alleviate age-related laxity, ptosis, and platysmal bands, they have limited efficacy on horizontal neck lines. Objectives: The purpose of this study was to investigate the efficacy, safety, and subject satisfaction of a combined treatment of non–cross-linked hyaluronic acid (HA) compound filling plus mesotherapy for the correction of horizontal neck lines, in comparison with BTX-A. Methods: This multicenter, randomized, evaluator-blinded, prospective study enrolled female patients with moderate-to-severe horizontal neck lines corrected with either 2 or 3 sessions of of non–cross-linked HA compound filling plus mesotherapy or 1 session of BTX-A injection. Improvement of the neck lines grades, Global Aesthetic Improvement Scale (GAIS), patient satisfaction, and adverse events (AEs) were evaluated and compared at 1, 3, 6, and 10 months after the final treatment. Results: Twenty-five patients received HA filling plus mesotherapy and 23 received BTX-A injection. Compared with BTX-A, the HA compound filling plus mesotherapy significantly improved the horizontal neck lines grades on all follow-up visits ( P = 0.000). Cases of different baseline grades (2, 2.5, and 3) demonstrated similar outcomes. The GAIS and patients' satisfaction ratings were significantly higher for the HA filling plus mesotherapy treatment group ( P = 0.000). Significantly higher pain ratings, higher incidence, and longer recovery of AEs (erythema, edema, and ecchymosis) were noticed in the combined treatment group ( P < 0.001). No serious AEs occurred. Conclusions: Compared with BTX-A, combined treatment with HA compound filling plus mesotherapy significantly improved moderate-to-severe horizontal neck lines and achieved a high level of patient satisfaction. Level of Evidence: 4: